Profile of postpartum patients with urinary retention at Koja Regional Hospital, Jakarta, Indonesia - Djusad, Suskhan; Meutia, Alfa Putri; Hakim, Surahman (Universitas Airlangga, 2024)
HIGHLIGHTS Maternal age and fetal birth weight are key risk factors for PPUR. Among 300 subjects, 63.7% experienced PPUR, identified using the Suskhan score, with catheterization as a useful tool for prevention and management planning. ABSTRACT Objective: Postpartum urinary retention (PPUR) is a common voiding disorder, defined as the inability to void spontaneously within 6 hours after delivery with a residual bladder volume exceeding 200 mL. High rates of PPUR in Indonesia indicate a need for greater awareness and intervention. This study aimed to assess the incidence and potential contributing factors of PPUR among postpartum patients at Koja Regional Hospital in Jakarta, Indonesia. Materials and Methods: A descriptive case-control study was conducted, involving women who experienced urinary retention following vaginal delivery at Koja Hospital, Jakarta, Indonesia between September and December 2022. Residual urine volume was measured by catheterization 6 hours after delivery. Data analysis, performed using SPSS version 22, included patient demographics and clinical factors such as maternal age, parity, gestational age, neonatal birth weight, and postvoid residual urine volume. These factors were analyzed to determine their association with PPUR. Results: Out of 300 subjects selected through consecutive random sampling, 63.7% experienced PPUR, while 36.3% had normal urinary function. Patients with a mean age of 26.91 ± 5.02 years (p = 0.000), primiparous status (first-time mothers) (p < 0.001), and a mean neonatal birth weight of 2980.95 ± 450.52 grams (p = 0.000) showed a higher risk of developing PPUR compared to other postpartum patients. Conclusion: The study indicated a significant association between postpartum urinary retention and maternal factors, including younger age, primiparity, and higher neonatal birth weight. Identifying these high-risk factors can enhance PPUR management, allowing healthcare providers to implement targeted monitoring and preventive measures, potentially improving postpartum outcomes in this patient population. This underscores the importance of monitoring these risk factors to better manage and potentially mitigate the incidence of PPUR.